Pengaruh Diabetes Self Manajemen Education (DSME) Terhadap Kepatuhan Minum Obat Pada Pasien Diabetes Tipe 2 di RSUD Bolaang Mongondow Utara - Vivi Meiti Berhimpong; Tinny Wilhelmina Mesbry Akay; Gratsia Victoria Fernandez (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Diabetes Mellitus (DM) has been recognized as one of the most challenging chronic diseases that can cause premature death and also as a major cause of blindness, heart disease, and kidney failure. The level of treatment adherence in chronic disease patients in developed countries is estimated to be low, even lower in developing countries including Indonesia. Giving Diabetes Self Management Education (DSME) to DM patients can obtain information related to DM self-care, knowledge, skills, and psychological status of patients have increased so that patients are compliant with treatment. This study aims to determine the effect of DSME on adherence to taking medication in Type 2 Diabetes patients at Bolaang Mongondow Utara Hospital. The design of this study was a pre-experimental approach with a one-group pre-post test design consisting of 50 respondents. The statistical test uses the Paired samples T-test. The results of the analysis show a p-value of 0.000 (<0.05), which means that there is a significant effect of DSME on medication adherence in DM patients. It is recommended that service institutions be able to provide DSME as an additional intervention for people with Diabetes Mellitus to increase adherence to taking medication so they can maintain glycemic control.